169 Similar Proportions Return to Work Following Fusion and Decompression Alone for Degenerative Grade 1 Lumbar Spondylolisthesis, Though the Trajectories Differ: An Analysis of the Quality Outcomes Database. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Chan, Andrew K.H; Bisson, Erica F; Bydon, Mohamad; Glassman, Steven D; Foley, Kevin T; Potts, Eric A; Shaffrey, Christopher I; Shaffrey, Mark E; Coric, Domagoj; Wang, Michael Y; Knightly, John J; Park, Paul; et al.
Abstract: INTRODUCTION: Low back pain is a leading cause of work-related disability in the United States and results in significant costs, including up to $20 billion annually due to lost productivity of the gainfully employed. Thus, return to work (RTW) is an important metric in the comparison of fusion versus decompression alone for grade 1 degenerative lumbar spondylolisthesis (DLS). METHODS: This was a retrospective analysis of a prospective registry. A total of 599 patients underwent surgery for grade 1 DLS at 12 high-enrolling sites. Baseline variables were collected. Employment was defined as being employed and actively working or employed and on leave at time of surgery. RTW was assessed at 3 and 12 mo following surgery. RESULTS: At baseline, 264 patients (44.1%) were employed. At baseline, there were a higher proportion of patients in the fusion cohort (219/462; 47.4%) who were employed compared with the decompression alone cohort (45/137; 32.8%; P  = .003). At 3 and 12 mo, for patients eligible for RTW, 62.6% and 74.3%, respectively, were able to do so. In a subgroup analysis of the decompression alone cohort, 64.1% demonstrated RTW at 3 mo with a rate that was similar at 12 mo (65.0%) ( P  = .94). In the fusion cohort, 62.3% demonstrated RTW at 3 mo with rates that continued to increase at 12 mo (75.8%) ( P  = .01). There were no significant differences in RTW between the decompression alone and fusion cohorts at 3 and 12 mo ( P  = .83 and P  = .30, respectively). CONCLUSION: At 12 mo, the overall RTW rate was equivalent between the decompression and fusion cohorts. The decompression alone cohort reached peak RTW at 3 mo, which remained stable at 12 mo. Though the fusion cohort showed similar RTW at 3 mo, the proportion continued to rise at 12 mo. Further study is required to determine RTW rates in longer follow-up.